2018
DOI: 10.1002/jcb.26807
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin E1 (RvE1) attenuates LPS induced inflammation and subsequent atrophy in C2C12 myotubes

Abstract: Resolution of inflammation is now known to be an active process which in part is instigated and controlled by specialized pro-resolving lipid mediators (SPM's) derived from dietary omega-3 fatty acids. Resolvin E1 (R E ) is one of these SPM's derived from the omega-3 fatty acid eicosapentaenoic acid. Using both molecular and phenotypic functional measures we report that in a model of Lipopolysaccharide (LPS) induced inflammation, R E attenuated mRNA levels of both interlukin-6 and monocyte chemoattractant prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 48 publications
5
25
0
Order By: Relevance
“…In the current study, serum cytokine levels were elevated in Ts65Dn mice and we further demonstrated that RvE1 administration restored normal levels of several cytokines involved in innate immunity (IL‐1ɑ, IL‐1β, IL‐6, and TNF‐ɑ). These results further indicate the potency of RvE1 in reducing inflammation in different tissues and corroborate previous findings in other mouse models of AD (Baker et al, ; Kantarci et al, ). Furthermore, modulating inflammation by chronically upregulating pro‐resolving mechanisms should be considered as a novel alternative to anti‐inflammatory approaches, such as chronic minocycline treatment (Hunter, Bachman, & Granholm, ; Hunter, Quintero, et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, serum cytokine levels were elevated in Ts65Dn mice and we further demonstrated that RvE1 administration restored normal levels of several cytokines involved in innate immunity (IL‐1ɑ, IL‐1β, IL‐6, and TNF‐ɑ). These results further indicate the potency of RvE1 in reducing inflammation in different tissues and corroborate previous findings in other mouse models of AD (Baker et al, ; Kantarci et al, ). Furthermore, modulating inflammation by chronically upregulating pro‐resolving mechanisms should be considered as a novel alternative to anti‐inflammatory approaches, such as chronic minocycline treatment (Hunter, Bachman, & Granholm, ; Hunter, Quintero, et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…RvD1 also directly reduced LPS stimulated mRNA expression of IL-6 and TNFα, as well as secretion of MCP-1 protein by C2C12 myotubes cultured in-vitro. Consistent with these observations, n-3 EPA derived resolvin E1 (RvE1) directly inhibits cytokine production by muscle cells (88).…”
Section: Discussionmentioning
confidence: 67%
“…Nonetheless, the current state of the art points to promising effects using different members of the SPM group and the eCB system on several chronic diseases. Therefore, the modulation of several SPM members and the eCB system may lead to potential routes for therapeutic development through the selective activation of anti-inflammatory bioactive lipids (lipoxins, resolvins, protectins, maresins, PEA, OEA) (64,(89)(90)(91)117) or the inhibition/antagonism of their receptors and enzymes (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…This process protected rodent brains from neuroinflammation, synaptic dysfunction, and cognitive decline (89). In an in vivo model of LPS-induced inflammation, the activation of resolvin E1 attenuated mRNA levels of several pro-inflammatory cytokines and chemokines (IL-6 and monocyte chemoattractant protein-1) in C2C12 skeletal muscle myotubes, preventing skeletal muscle atrophy in this cell type (90). In an adult male Sprague-Dawley rat model, lipoxin A4-a known SPM with powerful anti-inflammatory functions-exerted beneficial effects in cognitive impairment induced by chronic cerebral hypoperfusion (91).…”
Section: Specialized Pro-resolving Lipid Mediatorsmentioning
confidence: 99%
See 1 more Smart Citation